Dihydroartemisinin-Loaded Magnetic Nanoparticles for Enhanced Chemodynamic Therapy - Guo, Shengdi; Yao, Xianxian; Jiang, Qin; Wang, Kuang; Zhang, Yuanying; Peng, Haibao; Tang, Jing; Yang, Wuli (Frontiers in Pharmacology, 2020)
Recently, chemodynamic therapy (CDT) has represented a new approach for cancer treatment with low toxicity and side effects. Nonetheless, it has been a challenge to improve the therapeutic effect through increasing the amount of reactive oxygen species (ROS). Herein, we increased the amount of ROS agents in the Fenton-like reaction by loading dihydroartemisinin (DHA) which was an artemisinin (ART) derivative containing peroxide groups, into magnetic nanoparticles (MNP), thereby improving the therapeutic effect of CDT. Blank MNP were almost non-cytotoxic, whereas three MNP loading ART-based drugs, MNP-ART, MNP-DHA, and MNP-artesunate (MNP-AS), all showed significant killing effect on breast cancer cells (MCF-7 cells), in which MNP-DHA were the most potent. What’s more, the MNP-DHA showed high toxicity to drug-resistant breast cancer cells (MCF-7/ADR cells), demonstrating its ability to overcome multidrug resistance (MDR). The study revealed that MNP could produce ferrous ions under the acidic condition of tumor microenvironment, which catalyzed DHA to produce large amounts of ROS, leading to cell death. Further experiments also showed that the MNP-DHA had significant inhibitory effect on another two aggressive breast cancer cell lines (MDA-MB-231 and MDA-MB-453 cells), which indicated that the great potential of MNP-DHA for the treatment of intractable breast cancers.